2020
DOI: 10.29115/sp-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Online Survey Data: A Comparison of Data Quality among a Commercial Panel & MTurk

Abstract: Scholars seeking online data collection have sought the assistance of professional panels, which are commercial entities that recruit prospective research participants. Although not intended for recruiting participants, Amazon's Mechanical Turk (MTurk) service is a crowdsourcing platform that is being utilized for a lower cost. This study compares data collected from MTurk (N = 760) and a professional panel (N = 1,110) to assess aspects of data quality and respondent features. Results show that MTurk may produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…However, through SONA or MTurk (at home, over the internet), participants may feel less compelled to answer in a socially desirable manner, resulting in more accurate responses. It has also been shown that MTurk participants are slightly more demographically diverse [16,[18][19][20], which is something that we saw in our survey responses in terms of a wider age range for participants. However, the results from SONA and in-person surveys were similar [16].…”
Section: Related Worksupporting
confidence: 58%
“…However, through SONA or MTurk (at home, over the internet), participants may feel less compelled to answer in a socially desirable manner, resulting in more accurate responses. It has also been shown that MTurk participants are slightly more demographically diverse [16,[18][19][20], which is something that we saw in our survey responses in terms of a wider age range for participants. However, the results from SONA and in-person surveys were similar [16].…”
Section: Related Worksupporting
confidence: 58%
“…Participants were recruited for an online anonymous survey utilizing the Amazon Mechanical Turk (mTurk) crowdsourcing marketplace via Amazon.com. Previous research has indicated that mTurk samples provide socioeconomically and culturally diverse participants [25] and data quality are comparable to, or superior to, other platforms used to obtain survey participants [25][26][27]. For these reasons, mTurk was chosen in an effort to recruit a sample of dog owners that resembled the parameters of the United States demographic population.…”
Section: Methodsmentioning
confidence: 99%
“…This bias towards Left-leaning partisanship is not, however, attributed to the higher response rates from states that tend to vote Democrat in recent elections, an observation confirmed by simulating elections using the sample distribution and election data (43). Instead, this bias is likely the result of selfselection in non-random online surveys (44)(45)(46). Finally, the average and median income for the sample are $72,100 and $62,500 annually, compared to $88,600 and $62,800 in the 2019 5-year American Community Survey (42).…”
Section: Sample Description and Statisticsmentioning
confidence: 99%